THE EFFECTS OF CONSUME WATERMELON JUICE IN CHANGES BLOOD PRESSURE HYPERTENSION PATIENTS WITH OBESITY IN SRIMULYO VILLAGE REGION OF LOCAL GOVERNMENT CLINIC PIYUNGAN BANTUL YOGYAKARTA - Widodo, Andri; Sutanta, Sutanta (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2015)
ABSTRACT Background: Based on data from the Health National Research in 2007, prevalence of hypertension in the population aged > 18 years was 29.8% (based on measurements), total of 10 provinces have prevalence of hypertension in the population aged >18 years Riau, Bangka Belitung, Central Java, Region of Yogyakarta Special, East Java, West Nusa Tenggara, Central Kalimantan, South Kalimantan, Central Sulawesi and West Sulawesi. Objective: Knowing the Effects of Consume Watermelon Juice Against Blood Pressure Changes in Hypertensive Patient with Obesity in Srimulyo village, region of local government clinic piyungan Bantul Yogyakarta. Method: This research is Quasi Experiment and the methods using Non-equivalent Control Group. The Sum of Samples is 40 respondents who drawn by purposive sampling method. Data collected by the experimental observation method. Data analysis was performed with the Wilcoxon test. Results: Results of Wilcoxon test in the intervention group showed that the value of Z calculated for systolic -3.714 with P value 0.000 < α = 0.05 and for diastolic the value of Z Calculated -3.275 with P value 0.001 < α = 0.05. These results indicate that consuming watermelon juice can reduce the blood pressure in hypertensive patients with obesity. Conclusion: Consume watermelon juice has significant effect on blood pressure reduction in hypertensive patients with obesity. Keywords: Consume watermelon Juice, Hypertension Blood Pressure, Obesity.